Man Down : A guide for men on mental health - Hoare, Charlie (London : Vie, 2020)
Many men find it challenging to talk about their worries - and if you relate, then you're not alone. From tips on how to reach out, to advice on navigating mental health issues such as anxiety and depression, this book will offer tools and techniques to enable you to manage your mental health, and help you to live a happier, healthier life.
Keywords: Men -- Mental health -- Popular works; Depression in men -- Popular works; Mindfulness (Psychology); Health and Wellbeing